Comparison of Body Composition, Cardiovascular Fitness, Eating and Exercise Habits among University Students - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2015)
The present research aimed to compare the fitness parameters, nutritional patterns and exercise habits of students among School of Physical Education and Sports with regard to gender and three different departments. A total of 333 students (Trainer Education n=100, Physical Education and Sport Teaching n=90, and Sports Management n=150) participated in this research. Cardiovascular (CV) parameters, anthropometric and body composition measurements were taken. Analysis did not reveal significant department and gender interaction effects in terms of all parameters (p>0.05). Most of features were significantly different (p>0.05) between the genders, as expected. Exercises habits parameters were statistically (p<0.05) lower and CV parameters were slightly higher for the students in Sports Management program than that of other departments. As a conclusion, although there were some differences between the departments and gender,fitness properties,..nutritional patterns and exercise habits values of male and female participants were generally within a healthy profile.
Keywords: Blood Pressure; Heart Rate; Anthropometry; Food Habits; Physical Activity; PHYSICAL-ACTIVITY; GENDER-DIFFERENCES; COLLEGE-STUDENTS; SEX-DIFFERENCES; RISK-FACTORS; PREVALENCE; PATTERNS; LIFE